Assistance in the Implementation of a BUMDes Information System as an Effort to Strengthen Legal Compliance and Village Governance in Wirogunan Village, Kartasura, Sukoharjo - Suratno Pradotodiningrat; Thinesh AL R Ganesan; Aris Prio Agus Santoso (Abdi Masyarakat, 2026)
The management of Village-Owned Enterprises (BUMDes) in Wirogunan Village, Kartasura, Sukoharjo, is still predominantly conducted using manual systems, with limited utilization of information technology, low digital literacy among village officials, and suboptimal legal and administrative accountability. This condition creates a gap between the demands of digital-based good governance and existing practices at the village level. This community service program aims to enhance the institutional capacity of BUMDes through the implementation of an integrated information system to strengthen legality, transparency, and the effectiveness of village business management. The method used is a participatory-empirical approach, including needs assessment, system design, hybrid implementation (offline and online training), and evaluation through pre-test and post-test. The results show a significant improvement in participants’ understanding, where the average pre-test score of 45% increased to 82% in the post-test. This indicates that the mentoring program effectively improves digital literacy, legal awareness, and governance quality of BUMDes. The program contributes to the development of a digital-based BUMDes governance model that is more transparent, accountable, and sustainable.